Electronic Safety and Soundness : Securing Finance in a New Age - Glaessner, Thomas C.; Kellermann, Tom; McNevin, Valerie (Washington, DC: World Bank, 2013)
This monograph and its technical annexes identify and discuss four key pillars that are necessary to foster a secure electronic environment and the safety and soundness of financial systems worldwide. Hence, it is intended for those formulating policies in the area of electronic security and those working with financial services providers (such as executives and management). The detailed annexes of this monograph are relevant for chief information and security officers and others who are responsible for securing network systems. First, the monograph defines electronic finance (e-finance) and electronic security (e-security) and explains why these areas require attention. Next, it presents a picture of the emerging global security industry. Then, it develops a risk management framework to assist policymakers and practitioners in understanding the tradeoffs and risks inherent in using an open network infrastructure. It also provides examples of tradeoffs that may arise with respect to technological innovations, privacy, quality of service, and security in the design of an e-security policy framework. Finally, it outlines issues in four critical and interrelated areas that require attention in the building of an adequate e-security infrastructure. These are: (i) the legal, regulatory, and enforcement framework; (ii) external monitoring of e-security practices; (iii) public-private sector cooperation; and (iv) the business case for practicing layered e-security that will improve internal monitoring.